Cardiovascular complications in patients with cancer: focus on anthracycline-induced cardiotoxicity - I. T. Murkamilov; K. A. Aitbaev; V. V. Fomin; I. O. Kudaibergenova; F. A. Yusupov; Zh. A. Murkamilova (Кардиоваскулярная терапия и профилактика, 2021)
The article describes prevalence and risk factors of cardiovascular in patients with cancer. The problems of anthracycline-induced cardiotoxicity, the deleterious effects of doxorubicin on the heart, as well as the cardioprotective effects of beta-blockers and agents acting on the renin-angiotensin-aldosterone system pathway are discussed. By cardiotoxicity is implied the development of various adverse cardiovascular events against the background of drug therapy for cancer patients. Depending on the severity of myocardial damage, there are type I (anthracycline-mediated cardiotoxicity, myocardial damage is irreversible) and type II (trastuzumab-mediated cardiotoxicity, myocardial dysfunction is reversible) cardiotoxicity. Anthracycline-induced cardiotoxicity, in turn, is divided into acute, early-onset chronic and late-onset chronic. At the same time, the main mechanisms of anthracycline cytotoxicity in relation to healthy cardiomyocytes are stimulation of intracellular oxidative stress, a decrease in reduced glutathione concentration, inhibition of cell redox potential, and a change in iron metabolism. The article discusses in detail the risk factors (age, hypertension, diabetes, asymptomatic left ventricular dysfunction, documented cardiovascular diseases, heart failure, etc.), as well as the mechanisms and treatment of anthracycline-mediated cardiotoxicity.